Peran Teknologi dalam Membangun Generasi Muda Unggul dan Istiqamah: Perlakuan pada Ibu-Ibu Majlis Taklim Darul Aitam Nawiatu Al Rahmah (Dinar) - Nur Indah Yusari; Sri Rosmalina Soedjono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the role of technology in building a superior and steadfast young generation and to analyze how technology can be used to improve the quality of learning for the women of the Darul Aitam Nawiatu Al Rahmah (DINAR) majlis taklim (DINAR). This research uses a qualitative research method with a case study approach. The research results show that technology has a very important role in building a superior and steadfast young generation, namely by improving the quality of learning, facilitating access to information, and building learning communities. This research also shows that the ladies of the Darul Aitam Nawiatu Al Rahmah (DINAR) majlis taklim have used technology in learning activities, but still need improvement in terms of using technology more effectively and efficiently.